INCOME SMOOTHING DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA PADA PERUSAHAAN PARIWISATA YANG TERDAFTAR DI BURSA EFEK INDONESIA - M. Dwi Syahputra; Ngatemin Ngatemin (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2020)
This research was conducted with the aim to determine the effect of profitability, liquidity, financial leverage and ownership structure on income smoothing in Tourism Companies Listed on the Indonesia Stock Exchange. The approach used in this research is an associative approach. Data collection techniques in this study using documentation techniques. The total population of 23 companies there are 11 companies with 6 years of observation so the number of samples is 66 samples. Data analysis using multiple linear regression analysis of data processing in this study using the SPSS (Statistic Package for the Social Sciens) software program version 22.00. The results showed that partially Profitability had a positive and significant effect on Income Smoothing, Liquidity, Financial Leverage and Ownership Structure had no negative effect and no significant effect on income smoothing. Simultaneously Profitability, Liquidity, Financial Leverage and Ownership Structure jointly influence and significantly affect Income Smoothing in Tourism Companies listed on the Indonesia Stock Exchange for the period 2012-2017.